The Existence of Women in Socio-Political Movements in Indonesia in the Perspective of the Al-Qur'an: A Study of the Knowledge of the Ulema of the Ahlussunnah Wal Jamaah - Acim, Subhan Abdullah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discussed the issue of the existence of women in the political and socio-cultural arena in Indonesia, seen from the context of an Islamic religious perspective, namely a Koran following the guidance of the ulema Ahlussunnah Wal Jamaah. We get scientific evidence that supports this problem, sourced from books and publications of academic works in Islamic religious journals that we study under the phenomenological approach, namely getting several scientific pieces of evidence to answer the issues we are studying. In conclusion, we involve coding the data systematically. Carefully interpreting the data and evaluating it in depth, we finally took. Among other things is the conclusion that the existence of women in the political and socio-cultural arena in Indonesia, according to Islam, based on the advice of scholars, is highly expected for the contribution and trust of women. However, it has various requirements and criteria following the needs and the constitution in force in Indonesia. Thus, it is hoped that this study will be helpful for further studies on the existence of women in the political context and as other public figures based on religious guidance and the scholars of Ahlussunnah Waljamaah.